Optimization for the production of a dengue live-attenuated Quadrivalent vaccine in Vero cells grown on microcarriers - Shannon Haughney; Seth Clark; Elizabeth Carey; Nelson Lee Afanador; Victoria Stabile; Bernard Kang; Samantha Marrone; Jillian Shingler; Carl Hofmann; Christopher J. Wang; Christopher Ton (Vaccine: X)
Dengue is a mosquito-borne disease and is a major global health threat, especially in tropical and subtropical regions. In this study, we describe the optimization of virus production for a dengue live-attenuated quadrivalent vaccine candidate and demonstrate scalability of a stirred tank bioreactor serum-free microcarrier process. We utilized a design-of-experiment (DoE) methodology to optimize for pH and temperature and evaluate effect of Multiplicity of Infection (MOI) and Time of Infection (TOI) for each serotype during virus production in 2 L and 3 L bioreactors. The optimal pH and temperature for dengue virus production achieved ∼10× higher virus titer at peak virus production for all 4 serotypes compared to baseline condition. Different MOI and TOI did not impact peak virus production. Results from the DoE studies were successfully scaled to the 50 L Single-Use Bioreactor (SUB).